Projeto de um capacitor de filtro de saída para redução do flicker e análise da estimativa de vida útil de E-Caps para Aplicação em drivers para LED - Fernandes, Andressa da Silva (2020)
This work aims to analyze and design the output filter capacitor in ca-cc drivers for LEDs, in order to obtain the proportion of the output current ripple and the intrinsic resistance of the LEDs in the design of the output filter capacitor. Thus, it is possible to estimate the useful life of the E-Caps, making it possible to obtain the necessary parameters to allow the useful life of the E-Caps to be increased, enabling its application in systems that require a longer useful life. From all analyzes, a resonant AC-DC converter single-stage based topology of switched capacitors, has been proposed. For a power of approximately 90 W, the converter obtained an output current ripple of 49 mA and a final efficiency of 94.639%. However, due to the MOSFET's intrinsic capacitance interfering with the discharge of the input filter capacitor and resonating with the inductance, the presented circuit has been modified. With the modification of the proposed circuit, it was possible to eliminate the resonance between the input filter and the inductor capacitance. In this way, an output current ripple of 40 mA and a final efficiency of 94.1% were obtained. Prototypes were developed to evaluate and validate the proposals, while the results are properly presented and discussed.